Determinants of Gold Prices in Indonesia Period of 2018-2022 - Aprizal, Sigit; Harahap, Muhammad Nasim (Indonesia Banking School, 2025)
Gold plays a significant role in the economy, serving both as a store of value and an indicator of economic stability. This study aims to examine the impact of exchange rates, interest rates, the Indonesia Composite Stock Index (IHSG), and world oil prices on gold prices in Indonesia. The study utilizes monthly secondary data from January 2018 to December 2022 and applies the Vector Error Correction Model (VECM) for analysis. The long-run estimation results indicate that exchange rates, interest rates, and IHSG significantly influence gold prices, while world oil prices have a negative impact. In the short run, only the IHSG exhibits a significant negative effect. The Impulse Response Function (IRF) reveals that exchange rates and the IHSG generate negative shocks, whereas interest rates and world oil prices generate positive shocks to gold prices. Furthermore, the Variance Decomposition analysis shows that exchange rates contribute the most to gold price fluctuations, followed by the IHSG, interest rates, and world oil prices.